In Silico Molecular Engineering of Dysprosocenium-Based Complexes to Decouple Spin Energy Levels from Molecular Vibrations - Ullah, Aman; Cerdá, Jesús; Baldoví, José J; Varganov, Sergey A; Aragó, Juan; Gaita-Ariño, Alejandro (The journal of physical chemistry letters, 2019)
Molecular nanomagnets hold great promise for spintronics and quantum technologies, provided that their spin memory can be preserved above liquid-nitrogen temperatures. In the past few years, the magnetic hysteresis records observed for two related dysprosocenium-type complexes have highlighted the potential of molecular engineering to decouple vibrational excitations from spin states and thereby enhance magnetic memory. Herein, we study the spin-vibrational coupling in [(Cp )Dy(Cp*)] (Cp = pentaisopropylcyclopentadienyl, Cp* = pentamethylcyclopentadienyl), which currently holds the hysteresis record (80 K), by means of a computationally affordable methodology that combines first-principles electronic structure calculations with a phenomenological ligand field model. Our analysis is in good agreement with the previously reported state-of-the-art ab initio calculations, with the advantage of drastically reducing the computation time. We then apply the proposed methodology to three alternative dysprosocenium-type complexes, extracting physical insights that demonstrate the usefulness of this strategy to efficiently engineer and screen magnetic molecules with the potential of retaining spin information at higher temperatures.